Comparison of an in-house developed monitor unit double-check program for 3D conformal radiation therapy and treatment planning system verification. Issue 3 (8th January 2019) - Slassi, Noureddine; Ouabi, Hmad; El Khayati, Naïma
Abstract: Aim: The treatment planning system (TPS) plays a key role in radiotherapy treatments; it is responsible for the accurate determination of the monitor unit (MU) needed to be delivered to treat a patient with cancer. The main goal of radiotherapy is to sterilise the tumour; however, any imprecise dose delivered could lead to deadly consequences. The TPS has a quality assurance tool, an independent program to double check the MU, evaluate patient plan correctness and search for any potential error. Materials and methods: In this work, a comparison was carried out between a MU calculated by TPS and an independent in-house-developed monitor unit calculation program (MUCP). The program, written in Cplusplus (C++ Object-Oriented), requires a database of several measured quantities and uses a recently developed physically based method for field equivalence calculation. The ROOT CERN data analysis library has been used to establish fit functions, to extend MUCP use to a variety of photon beams. This study presents a new approach to checking MU correctness calculated by the TPS for a water-like tissue equivalent medium, using our MUCP, as the majority of previous studies on the MU independent checks were based on the Clarkson method. To evaluate each irradiated region, four calculation points corresponding to relative depths under the water phantom were tested for several symmetric, asymmetric, irregular symmetric and asymmetric field cases. A comparison of MU for each radiation fields from readings of the TPS and the MUCP was undertaken. Results: A satisfactory agreement has been obtained and within the required standards (3%). Additional experimental measurements of dose deposited in a water phantom showed a deviation of <1·6%. Findings: The MUCP is a useful tool for basic and complex MU verification for 3D conformal radiation therapy plans.